miR‐4448/Girdin/Akt/AMPK axis inhibits EZH2‐mediated EMT and tumorigenesis in small‐cell lung cancer - Nobuyuki Koyama; Yuichi Ishikawa; Hiromitsu Ohta; Takuya Aoki; Hiroyuki Kyoyama; Kazutetsu Aoshiba; Kazutsugu Uematsu (Cancer Medicine)
Abstract Background Small‐cell lung cancer (SCLC) shows high enhancer of zeste homolog 2 (EZH2) expressions. EZH2‐mediated epigenetics promote epithelial‐mesenchymal transition (EMT), enhancing invasive and metastatic potential in malignancies. MicroRNAs (miRNAs), small noncoding RNAs, modulate EMT, determining tumor phenotypes. However, the association between miRNAs and EZH2 in SCLC remains to be clarified—we aimed to identify a novel tumorigenic mechanism through miRNAs, EZH2, and EMT in SCLC, leading to future therapeutic applications. Methods We analyzed EZH2 and E‐cadherin expressions in lung cancer cell lines and tumor tissues from 34 SCLC patients and confirmed EZH2 siRNA‐mediated EMT inhibition. miRNA expression profiles were compared between EZH2 knockdown SCLC cells and negative control SCLC cells using miRNA array. We identified a target miRNA of EZH2 showing expressional differences in EZH2‐knockdown cells and analyzed the impact of the miRNA on EZH2‐mediated EMT and tumorigenesis. Results All SCLC cells showed increased EZH2 and decreased E‐cadherin expressions. SCLC tissues had higher EZH2 and lower E‐cadherin expressions than other lung cancer tissues. miRNA array revealed that miR‐4448 expression increased in EZH2‐knockdown SCLC cells. miR‐4448 overexpression reduced tumor cell growth and prevented EMT. miR‐4448 bound to the 3′UTR of the girdin gene and suppressed its expression, thereby decreasing Akt phosphorylation at Ser473. Attenuated Akt phosphorylation resulted in AMP‐activated protein kinase (AMPK) phosphorylation at Thr172 and 183, enhancing EZH2 phosphorylation at Thr311. Conclusion SCLC characterized high EZH2 expression and promoted EMT, compared with non‐small cell lung cancer. miR‐4448 inhibited Girdin expression, reducing Akt phosphorylation, and enhancing AMPK and EZH2 phosphorylation. Eventually, miR‐4448 prevented EZH2‐mediated EMT and tumorigenesis by modulating the Girdin/Akt/AMPK axis in SCLC. miR‐4448 might be a potential SCLC inhibitor.